Characteristics, treatments, and prognosis of a critical illness polyneuromyopathy patient with positive anti‐GM1 after severe traumatic brain injury: A case report. (28th March 2021) - Luo, Jiemin; Xia, Zhiyuan; Che, Yanjun; Zhou, Ke
Abstract: To investigate the clinical features, treatment and prognosis of critical illness polyneuromyopathy (CIPNM) in patients with severe traumatic brain injury (sTBI) who had positive anti‐ganglioside GM1 (anti‐GM1) antibody IgG. A case of CIPNM with positive anti‐GM1 antibody IgG was retrospectively analysed and followed‐up for 30 months. After 1 week of treatment with large dose of short‐term glucocorticoid and human immunoglobulin, the muscle strength of both lower extremities was restored to grade 1. Three months later, the muscle strength and muscle tension of the patient's limbs returned to normal except for grade 3 of bilateral dorsal extensor muscle strength. In addition, the patient can walk alone with a waddling gait. After 30 months, there was no recurrence. The application of large dose of short‐term glucocorticoid and human immunoglobulin to CIPNM that are positive for anti‐GM1 antibodies may be an effective treatment. Abstract : We found that positive anti‐GM1 antibody in patients with CIPNM, which suggests that anti‐GM1 antibody may be related to CIPNM. The application of high‐dose cortisol and human gamma‐immunoglobulin to CIPNM that are positive for anti‐GM1 antibodies may be an effective treatment.